2020
DOI: 10.21307/jofnem-2020-100
|View full text |Cite
|
Sign up to set email alerts
|

Nematode trophic structure in the phytotelma of Neoregelia cruenta (Bromeliaceae) in relation to microenvironmental and climate variables

Abstract: The term phytotelma (pl. phytotelmata) designates a plant-associated reservoir of fresh water and organic debris. Phytotelmata in tank bromeliads are abundant in tropical forests, and they provide shelter, food, and water for many metazoans. Among the invertebrates known to inhabit phytotelmata, nematodes are the least studied, despite their important role in nutrient and energy cycles in freshwater ecosystems. This study was conceived to characterize the nematode trophic structure in the phytotelma of the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Samples were collected in the terrestrial bromeliad Neoregelia cruenta (R. Graham) L. B. Smith, which thrives abundantly in the RJNP, shaded by short trees and shrubs. Only mature plants with inflorescence were sampled because this phenological stage is known to support a more abundant nematode community ( Almeida and Souza, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Samples were collected in the terrestrial bromeliad Neoregelia cruenta (R. Graham) L. B. Smith, which thrives abundantly in the RJNP, shaded by short trees and shrubs. Only mature plants with inflorescence were sampled because this phenological stage is known to support a more abundant nematode community ( Almeida and Souza, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown that in all phytotelmata, bacterial, and hyphal feeder nematodes predominate over plant feeders, unicellular eukaryote feeders and carnivores. Seasonal changes in nematode abundance (total and per trophic group) have been reported in some studies (Ptatscheck and Traunspurger, 2015;Robaina et al, 2015;Zotz and Traunspurger, 2016), but not in others (Ptatscheck and Traunspurger, 2014;Almeida and Souza, 2020).…”
mentioning
confidence: 92%
See 3 more Smart Citations